Lingkungan Keluarga Dalam Pendidikan Anak Usia Dini Menurut Perspektif Hadis - Suryani, Suryani (DAWUH : Islamic Communication Journal, 2022)
The purpose of this research is to find out what are the traditions of Early Childhood Education in the perspective of hadiths. The family environment is the first and foremost educational environment, because it is in this family that children receive guidance and education. The family can also be the first and main container for the growth and development of children. This hadith is a very emphatic hadith which shows that noble character is a very great worship, even among the greatest worship. Among the moral education that needs to be given to early childhood, among others, is morality towards parents, family, friends, teachers, the environment and society in general. Education about love for family is very important to give to early childhood, so that children from an early age understand their rights and obligations in family life.